الاحتياجات التدريبية في أداء الموظفين في المؤسسة الوطنية للنفط بليبيا دراسة تحليلية - Abdulgader M.Ali Hwedi (Universiti Sains Islam Malaysia, 2024)
The study aimed to identify the impact of the training needs of organizational performance in the National Oil Corporation - Libya. The study population consist of (801) employees of the National Oil Corporation employees in Libya, the sample was selected from (259) employees. Where it has been depending on SPSS program, for statistical analysis, and the resulting unilateral variance alfa analysis was (9.23) the ratio alpha (0.000), which indicates the acceptance of the main hypothesis, which states that there is a statistically significant impact to determine the training needs of the organizational performance within the National Oil Corporation. Since the results of the coefficient of determination "R2" was (0.146), which shows that independent variables explain (14.6%) of the changes that occur of the dependent variable values, organizational performance and the rest (85.4%), while the correlation coefficient (a) was (0.381), there was a statistically significant relationship between the use of scientific methods to identify training needs and organizational performance. As the results of the beta values = (. 308), T = (4.79), the degree of scientific standards used in determining training needs were the arithmetic mean (3.5159) and standard deviation (1.0423) and (70%) of the answer to the sample, the study showed a positive relationship between the use of standards in organizational performance and training needs, the study found there are statistically significant differences at the moral level of (0.05) or less in the trends of the sample on the study attribute the axes demographic variables except gender and age. The study recommends the need to revisit the training programs to fit the most important training needs, and the leaders attention with the help of experts in the collection needed to assess the training needs of the information, it is advisable to apply the theory of TNA.